2010
DOI: 10.1111/j.1478-3231.2009.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status: its influence on the outcome of patients undergoing liver transplantation

Abstract: The present data suggest that recipients' malnutrition should be taken into account as a factor that increases complications and costs after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
181
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 33 publications
(44 reference statements)
1
181
3
8
Order By: Relevance
“…4,5 Notably, the latter aspect could have been responsible of the difference between our findings and the results reported by previous meta-analyses as concerns the mortality risk. In fact, we found a pretty robust increase in OR at 30 days, when either BMI ≥30 and 40 were evaluated (1.90; CI: 1.38, R E F E R E N C E S 1 and prevention of relapse following surgery in Crohn's disease, 2 although its efficacy in the induction and maintenance of remission in Crohn's disease remains disputed.…”
contrasting
confidence: 98%
See 1 more Smart Citation
“…4,5 Notably, the latter aspect could have been responsible of the difference between our findings and the results reported by previous meta-analyses as concerns the mortality risk. In fact, we found a pretty robust increase in OR at 30 days, when either BMI ≥30 and 40 were evaluated (1.90; CI: 1.38, R E F E R E N C E S 1 and prevention of relapse following surgery in Crohn's disease, 2 although its efficacy in the induction and maintenance of remission in Crohn's disease remains disputed.…”
contrasting
confidence: 98%
“…3 In addition, the drug may be of benefit in a subset of patients with irritable bowel syndrome. 4,5 Diverticular disease is a chronic disorder of the lower GI tract.…”
mentioning
confidence: 99%
“…Some studies suggest that a poor nutritional status, for instance, as reflected by the subjective global assessment, impairs posttransplantation outcomes (41)(42)(43). However, these measures are frequently considered as subjective (44).…”
Section: Discussionmentioning
confidence: 99%
“…78,94,95 Malnutrition is known to lead to glycogen depletion, and this has been suggested to result in increased plasma lactate: pyruvate ratios during the an hepatic phase and to favor the development of a post-operative systemic inflammatory response syndrome and multi-organ failure in these patients. 96 In a prospective study, Merli et al 97 presented data suggesting that malnutrition should be taken into account as a factor that increases both costs and post-transplant complications. Moreover, they demonstrated that malnutrition…”
Section: Malnutrition and Outcome Following Liver Transplantationmentioning
confidence: 99%